Interlayer hybridization in a van der Waals quantum spin-Hall insulator/superconductor heterostructure - Bussolotti, Fabio (2023)
In this work, we present an angle-resolved photoemission spectroscopy study of a 1T′-WTe2 monolayer epitaxially grown on NbSe2 substrates, a prototypical quantum spin Hall insulator (QSHI)/superconductor heterojunction. Angle-resolved photoemission spectroscopy data indicate the formation of electronic states in the bulk bandgap of WTe2, which are absent in the nearly free-standing WTe2 grown on the highly oriented pyrolytic graphite substrate, where an energy gap of ∼100 meV is reported. The results are explained in terms of hybridization effects promoted by the QSHI-superconductor interaction at WTe2/NbSe2 interfaces, in line with recent scanning probe microscopy investigation and theoretical band structure calculations. Our findings highlight the important role of interlayer interaction on the electronic properties and ultimately on the engineering of topological properties of the QSHI/superconducting heterostructure.